Hello, @Arnab! I suppose the following is the answer you're looking for. First define f:
f(x) = x^2 + 1
Now compose simply by writing:
f2(x) = f(f(x))
f3(x) = f(f(f(x)))
As you might guess, f2 is the composition f∘f with itself, while f3 is the composition f∘f∘f.
The same mechanism works for different functions. Let's define
f(x) = x^2 + 1
g(t) = t^3
Then you can write
fg(t) = f(g(t))
gf(x) = g(f(x))
The first one will give you t6+1, while the second will give you (x2+1)3.
I hope this helps!
![]() | 2 | No.2 Revision |
Hello, @Arnab! I suppose the following is the answer you're looking for. First define f:
f(x) = x^2 + 1
Now compose simply by writing:
f2(x) = f(f(x))
f3(x) = f(f(f(x)))
As you might guess, f2 is the composition f∘f (f with itself, itself), while f3 is the composition $f\circ f\circ f$.f(threetimesf$).
The same mechanism works for different functions. Let's define
f(x) = x^2 + 1
g(t) = t^3
Then you can write
fg(t) = f(g(t))
gf(x) = g(f(x))
The first one will give you t6+1, while the second will give you (x2+1)3.
I hope this helps!